2007
DOI: 10.1099/jmm.0.46973-0
|View full text |Cite
|
Sign up to set email alerts
|

An antifungal protein from Escherichia coli

Abstract: A cytosolic protein was purified from Escherichia coli BL21 that demonstrated potent antifungal activity against pathogenic strains of Aspergillus fumigatus, Aspergillus flavus, Aspergillus niger and Candida albicans. The MIC of purified protein from E. coli BL21 (PPEBL21) against Aspergillus species and C. albicans was 1.95-3.98 and 15.62 mg ml "1 , respectively. In vitro toxicity tests demonstrated no cytotoxicity of PPEBL21 to human erythrocytes up to the tested concentrations of 1250 mg ml "1. Amphotericin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 36 publications
3
17
0
Order By: Relevance
“…The protein profile of the crude lysate gave large number of bands when run on SDS-PAGE and the fractified peak with the highest antifungal activity showed many protein bands in the molecular mass range of 20 -45 KDa. This result was in accordance with that observed by Yadav et al (2005a and2007) showing that the fractifaction of E. coli BL21 lysate showed 5 fractions of protein. The protein profile of crude E. coli BL21 lysate and the active fraction with antifungal activity showed that crude lysate gave various bands when run on SDS-PAGE, while the active fraction with antifungal activity demonstrate two major bands in the molecular mass range of 29 to 43 KDa.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The protein profile of the crude lysate gave large number of bands when run on SDS-PAGE and the fractified peak with the highest antifungal activity showed many protein bands in the molecular mass range of 20 -45 KDa. This result was in accordance with that observed by Yadav et al (2005a and2007) showing that the fractifaction of E. coli BL21 lysate showed 5 fractions of protein. The protein profile of crude E. coli BL21 lysate and the active fraction with antifungal activity showed that crude lysate gave various bands when run on SDS-PAGE, while the active fraction with antifungal activity demonstrate two major bands in the molecular mass range of 29 to 43 KDa.…”
Section: Discussionsupporting
confidence: 82%
“…In the present study, crude lysate was non toxic up to a test concentration of 200 µg/ml on the other hand, the fractified fraction with antifungal activity FΙ showed no toxicity with all tested concentrations up to 2000 µg/ml against erythrocytes, as compared to this results with that obtained by Yadav et al (2005a and2007) who showed that E. coli BL21 total lysate and completely purified fraction with antifungal activity PPEBL21 were non toxic up to a test concentration of 1250 µg/ml to human erythrocytes. These results gave evidence that the partially purified L. fermentum lysate is totally safe for producing potent antifungal compound.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Dissimilarly, many authors worked on using B. pumilus in order to obtain bioactive secondary metabolites acting against different pathogenic fungi regardless the biotoxicity of these metabolites towards human or plant (Ghasemi et al, 2012;Bullerman, 1997, 1998;Munimbazi and Bullerman, 1998). On the other hand, Yadav et al (2007) purified a cytosolic protein from E. coli BL21; it demonstrated potent antifungal activity against pathogenic strains of Aspergillus species (A. fumigatus, A. flavus, A. niger) and C. albicans with MIC of 1.95 to 3.98 and 15.62 mg ml -1 , respectively, and it showed no cytotoxicity up to 1250 mg ml -1 in vitro toxicity tests, which is very high concentration compared to the LC 50 of the antifungal agent of B. pumilusSMH101 (Table 4).…”
Section: Types Of Antifungal Agentmentioning
confidence: 99%
“…Yadav et al (2010Yadav et al ( , 2007 reported that cytosolic proteins of E. coli are responsible for antifungal potential against pathogenic strains of Aspergillus fumigatus, Aspergillus flavus, A. niger and Candida albicans. Also, Mushtaq et al (2010) reported that E. coli showed almost complete inhibition against pathogenic fungi such as A. niger and A. flavus.…”
Section: Staphylococcus Aureus (Mrsa) E Coli M2 Effectivelymentioning
confidence: 99%